Perceived Service Quality and Consumer Satisfaction : An Empirical Study from Direct to Home (DTH) TV Industry - Kaur, Kamalpreet; Singh, Amar Inder (Indian Journal of Marketing, 2017)
This study attempted to find the relationship between perceived service quality and consumer satisfaction in the direct to home TV Industry. The study was based on primary data, which was collected with the help of a structured questionnaire from top three urban districts, that is, Ludhiana, Amritsar, and Sahibzada Ajit Singh Nagar of Punjab. The sample size of 500 respondents was selected on the basis of convenience sampling. To measure the perceived service quality, theÂ SERVQUAL scale was used by using its five dimensions, that is, tangibility, reliability, responsiveness, assurance, and empathy. Consumer satisfaction was measured on the 7- point Likert type scale. The data was analyzed by using the statistical tools like correlation and stepwise regression. The results found that in all the three cases - whether the consumers shifted from Cable to DTH, Set Top Box to DTH, and Doordarshan to DTH, reliability was the most significant dimension of service quality, which had an impact on consumer satisfaction. This study will help the DTH companies to frame their marketing strategies to increase their service quality on the specified dimensions so that the consumers will get higher satisfaction and remain loyal to the company. This study will also be useful for the DTH players to retain the present customers and to increase their market share.